Facile fabrication of Tl4HgI6 nanostructures as novel antibacterial and antibiofilm agents and photocatalysts in the degradation of organic pollutants. Issue 10 (26th March 2021) - Karami, Maryam; Ghanbari, Mojgan; Alshamsi, Hassan Abbas; Rashki, Somaye; Salavati-Niasari, Masoud
Abstract : Nano-Tl4 HgI6 was fabricated via a co-precipitation route. It showed efficient antibacterial activity against Gram-negative and Gram-positive bacteria. Its photocatalytic activity indicated the highest degradation for RhB of around 78%. Abstract : Semiconductor photocatalysis has drawn much consideration from scientists in the current decade. The photocatalytic procedure is an eco-friendly process that has been recognized as a promising alternative for the removal of several hazardous pollutants. The deficiencies of current photocatalytic systems, which limit their technical applications, include low-utilization of visible radiation, fast charge recombination, and low migration capacity of the photo-induced electron-holes. In the present study, Tl4 HgI6 nanostructures have been successfully fabricated through a simple precipitation route. The impact of the TlI stoichiometric ratio to HgI2, and the types of surfactants was explored in terms of the purity, structure, scale, and shape of the samples. The bandgap of nano-Tl4 HgI6 was evaluated via diffuse reflectance spectroscopy (DRS) to be around 2.05 eV, which is suitable for photocatalytic performance. Raman spectroscopy results corroborated the X-ray diffractometry results and revealed that the Tl4 HgI6 nanoparticles were successfully fabricated. The structure, shape, and scale of the products were studied by field emission scanning electron microscopy. It was observed that different factors had a notable effect on the morphology and size of the products. The maximum antibacterial activity of Tl4 HgI6 was determined against S. aureus, E. coli, and M. catarrhalis. These outcomes demonstrated that Tl4 HgI6 displays efficient bactericidal activity against Gram-positive and Gram-negative microorganisms. The anti-biofilm activity revealed that the best biofilm decrease was recognized at higher Tl4 HgI6 concentrations (2 × the minimum inhibitory concentration). This represents the first study of the investigation of the photocatalytic activity of Tl4 HgI6 nanostructures. The photocatalytic performance was studied to eliminate various dyes and with different dosages of the catalyst under UV and visible light. The results indicate that these nanoparticles can remove organic dyes with high efficiency.